Evaluation of water quality in the water channel “La Ovejera” located in Campoalegre – Huila using aquatic bioindicators - Moreno, Yoly Dayana
Water is a strategic resource vital to the development and maintenance of living things. The water sources are subjected daily to severe human intervention causing changes in the quality of freshwater systems, directly affecting aquatic biota; therefore, aquatic bioindicators, such as macroinvertebrates, are used as an ideal tool for assessing the degree of pollution in a water body since they allow to quickly and economically identify the ecological status of the water source. In this study the effect of human activities on the macroinvertebrate communities inhabiting the tributary and effluent water channel “La Ovejera” was evaluated. For assessing the water quality a BMWP (Biological Monitoring Working Party Score System) index for water sources in Colombia was used. According to the analysis of macroinvertebrates collected in the water channel “La Ovejera”, it was found that the tributary of the channel has clean water quality while the effluent showed moderately polluted quality. These results suggest that different anthropogenic activities along the channel “La Ovejera” are affecting the structure of communities of aquatic macroinvertebrates, in consequence there are changes in the ecological balance and deterioration of the quality of this water source.